2017
DOI: 10.1016/j.jhsa.2016.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Elbow Instability: Anatomy, Biomechanics, Diagnostic Maneuvers, and Testing

Abstract: The elbow comprises a complex of bony and ligamentous stabilizers that provide both primary and secondary constraints to elbow instability. Through trauma and overuse, classic instability patterns arise by loss of these important stabilizers. The diagnosis of elbow instability can made using specific examination maneuvers and testing to diagnose the clinical pattern. This article reviews the elbow’s unique anatomy and biomechanical characteristics and these are applied when reviewing the maneuvers and testing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(61 citation statements)
references
References 24 publications
1
54
0
Order By: Relevance
“…While compared with isolated radial head fractures, the TTI involves more structural damage of the elbow, including ligaments and coronoid process. Damage to these structures increases the valgus stress on the radial head [ 23 , 24 ]. We also found that Mason III fractures were accompanied by more severe damage to the capsuloligamentous structures, reflecting higher energy damage to the elbow structures compared to Mason I or II fractures.…”
Section: Discussionmentioning
confidence: 99%
“…While compared with isolated radial head fractures, the TTI involves more structural damage of the elbow, including ligaments and coronoid process. Damage to these structures increases the valgus stress on the radial head [ 23 , 24 ]. We also found that Mason III fractures were accompanied by more severe damage to the capsuloligamentous structures, reflecting higher energy damage to the elbow structures compared to Mason I or II fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the shoulder, the elbow allows a more constrained range of motion. Indeed, it is commonly approximated as a hinge joint with one principal rotational degree of freedom (DOF), corresponding to the flexion–extension motion (0–140°) [1,2]. A second DOF consisting in pronation–supination is commonly referred to the wrist joint, even if the elbow partially cooperates during the motion.…”
Section: Introductionmentioning
confidence: 99%
“…Elbow muscles are dynamic stabilizers. Among them, the lateral extensor musculature (extensor carpi ulnaris, extensor digitorum communis, extensor carpi radialis brevis, extensor carpi radialis longus, anconeus) resists varus forces, while the medial flexor musculature (the flexor carpi ulnaris, flexor carpi radialis, flexor digitorum superficialis, pronator teres) resists valgus forces [2].…”
Section: Introductionmentioning
confidence: 99%
“…The elbow joint comprises ligamentous and bony stabilizers that furnish both primary and secondary stability during flexion. The ulnohumeral articulation, the anterior bundle of the medial collateral ligament (AM-CL) and the lateral collateral ligament (LCL) complex are the 3 primary static constraints, while the radiocapitellar articulation, the common flexor tendons, the common extensor tendons and the joint capsule are the secondary static constraints 1 . The muscles which cross the elbow joint represent the dynamic stabilizers, and their role has already been investigated in 2,3 .…”
Section: Introductionmentioning
confidence: 99%